Gender and age wage-productivity gaps in intangible and non-intangible work occupations - Istenič, Tanja (Economic and business review, 2024)
The paper focuses on gender- and age-related wage-productivity gaps in intangible and non-intangible work occupations using the 2017 Slovenian linked employer-employee microdata for privately owned firms. Comparing employees based on age, gender and occupation, our results show that, in general, there are wage gaps in favour of men, with the exception of individuals aged 50 or older who belong to the intangible capital group, where the wages of men and women are almost equal. There are also significant wage gaps in favour of older workers, with the exception of women in non-intangible occupations, where those aged 30-49 and those aged 50+ earn almost the same. Comparing the productivity of workers using value added decomposition method and based on age, gender and occupation, in general we find that gender and age gaps are more pronounced. For example, women tend to be more productive than men, with the exception of men under the age of 30 in non-intangible work occupations. Similarly, older workers tend to be less productive than their younger counterparts, with the exception of women aged 30-49 compared to women under 30 in non-intangible work occupations. Moreover, age-related wage productivity gaps are higher for intangible than for non-intangible worker occupations.
Keywords: ageing; gender; osebni dohodek; personal income; productivity; produktivnost; Slovenia; Slovenija; spol; staranje